2021
DOI: 10.1002/adhm.202100639
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes and Extracellular Vesicles as Drug Delivery Systems: A Comparison of Composition, Pharmacokinetics, and Functionalization

Abstract: Over the past decades, lipid-based nanoparticle drug delivery systems (DDS) have caught the attention of researchers worldwide, encouraging the field to rapidly develop improved ways for effective drug delivery. One of the most prominent examples is liposomes, which are spherical shaped artificial vesicles composed of lipid bilayers and able to encapsulate both hydrophilic and hydrophobic materials. At the same time, biological nanoparticles naturally secreted by cells, called extracellular vesicles (EVs), hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(152 citation statements)
references
References 253 publications
0
116
0
5
Order By: Relevance
“…Liposomes which are artificial spherical vesicles prepared from naturally derived phospholipids are the most widely investigated and well-established drug delivery carriers used in clinics to treat various cancers due to their biocompatibility, specifically being non-immunogenic, non-toxic, and biodegradable. In addition, liposomes serve as sustained release systems providing protection against degradation and increased the time in circulation (Moosavian et al, 2021;van der Koog et al, 2021). In this sense, our group recently demonstrated that liposome encapsulated DSF a relatively extended half-life in serum and a significantly increased anticancer efficacy in in vitro and in vivo breast cancer mouse models (Liu et al, 2014).…”
Section: Nanotechnology-based Formulation Strategies For Delivery Of Disulfirammentioning
confidence: 99%
“…Liposomes which are artificial spherical vesicles prepared from naturally derived phospholipids are the most widely investigated and well-established drug delivery carriers used in clinics to treat various cancers due to their biocompatibility, specifically being non-immunogenic, non-toxic, and biodegradable. In addition, liposomes serve as sustained release systems providing protection against degradation and increased the time in circulation (Moosavian et al, 2021;van der Koog et al, 2021). In this sense, our group recently demonstrated that liposome encapsulated DSF a relatively extended half-life in serum and a significantly increased anticancer efficacy in in vitro and in vivo breast cancer mouse models (Liu et al, 2014).…”
Section: Nanotechnology-based Formulation Strategies For Delivery Of Disulfirammentioning
confidence: 99%
“…Due to their amphiphilic properties, liposomes form an aqueous inner phase surrounded by lipophilic bilayer(s) that can encapsulate hydrophilic molecules in the inner phase and hydrophobic molecules in the bilayer(s). Liposomes have been widely applied as DDS to deliver chemicals, proteins, peptides, and genetic molecules because of their biocompatible nature and capability to accommodate high content of payloads protecting from degradation [13,15]. There exist commercial liposomal therapeutics in clinical applications, indicating excellent biocompatibility and versatility as DDS [13,15].…”
Section: Liposomal Vesicle-integrated Scaffolds For Bone Regenerationmentioning
confidence: 99%
“…Liposomes have been widely applied as DDS to deliver chemicals, proteins, peptides, and genetic molecules because of their biocompatible nature and capability to accommodate high content of payloads protecting from degradation [13,15]. There exist commercial liposomal therapeutics in clinical applications, indicating excellent biocompatibility and versatility as DDS [13,15]. Biomaterial scaffolds incorporating liposomes have been developed to synergize therapeutic effects and mechanical supports for efficient bone regeneration.…”
Section: Liposomal Vesicle-integrated Scaffolds For Bone Regenerationmentioning
confidence: 99%
See 2 more Smart Citations